Situational Judgment Tests - CHAN, David (Institutional Knowledge at Singapore Management University, 2005)
The inclusion of situational judgment tests (SJTs) in a battery of predictor measures has become increasingly common in personnel selection research and practice (e.g., Chan & Schmitt, 2002; Phillips, 1992; Pulakos & Schmitt, 1996; Weekley & Jones, 1999). Unlike cognitive ability and personality measures which have an extensive literature and large database, the empirical evidence on SJTs is much less well established and the theoretical or conceptual underpinnings of SJTs are much less well understood. This chapter summarizes what we now know and do not know about SJTs and identifies specific directions for future research. We begin with a summary of the research on the criterion-related validity of SJTs. This is followed by a discussion of several important issues involving the construct validity of SJTs that have not been adequately addressed in extant research. The chapter ends with an agenda for future research that, if effectively implemented, should contribute to our understanding and effective use of SJTs in personnel selection.